1999
DOI: 10.1076/jcen.21.4.477.876
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Memory Deficits in Patients with Fibromyalgia Syndrome

Abstract: The present study compared 30 patients with Fibromyalgia Syndrome (FS) to 30 healthy control subjects matched for age, sex, and estimated intellectual level on standardized measures of attention, concentration, and memory as well as subjective ratings of memory abilities and sleep quality. In addition, in order to investigate the relationship between cognitive functioning and other physical and psychological symptoms, subjects with FS completed psychological measures of pain severity, trait anxiety, and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
158
6
20

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(201 citation statements)
references
References 28 publications
17
158
6
20
Order By: Relevance
“…In their subsequent work, these authors replicated this finding using the same measure [12]. Other studies using different measures such as the paced auditory serial addition test [4,5], and the reading span test [7], reported reduced performance in patients with FM.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In their subsequent work, these authors replicated this finding using the same measure [12]. Other studies using different measures such as the paced auditory serial addition test [4,5], and the reading span test [7], reported reduced performance in patients with FM.…”
Section: Introductionsupporting
confidence: 57%
“…Other core symptoms, include fatigue, sleep disturbance, and frequently reported cognitive complaints or ''fibrofog'' [2,3]. These cognitive complaints have been confirmed by objective measures, and those studies have revealed that patients with FM have impairments in psychomotor speed [4], attention [5], working memory [6] and long-term verbal memory [7].…”
Section: Introductionmentioning
confidence: 99%
“…First of all, we evaluated patients with chronic pain in general, not a specific group as fibromyalgia or lumbar pain 5,6,7 . In addiction, we intended to investigate other cognitive domains rather than only working memory 12 , including tests that could be brief and easily administered by non specialized clinicians of a primary care health service.…”
Section: Discussionmentioning
confidence: 99%
“…There is a predominance of affected women, aged 45 to 65 years 4 . Patients with chronic pain frequently report cognitive complaints that impair social situations and daily life activities 5,6,7 . The exact mechanism underlying the complex relationship between pain, memory and attention is not fully understood, however it is known that the same neural networks used for many cognitive functions are also used for nociceptive functions.…”
mentioning
confidence: 99%
“…However, it remains to be understood which processes in normal aging affect proper name retrieval specifically. Increased proper name retrieval complaint may be associated with various conditions, some of which, such as depression, fatigue, pain or sleep disorder [1,44,45], may be treated efficiently. Interestingly, the level of complaint did not differ between demented and nondemented subjects.…”
Section: Discussionmentioning
confidence: 99%